Insulin resistance, does it exist? The current state of knowledge - Michalska, Milena; Stec, Albert; Lubaszka, Zuzanna; Żurek, Urszula; Fiega, Jakub; Szewczyk, Dorota; Gil, Aleksandra; Sikorski, Piotr; Sikorska, Ewa (Journal of Education, Health and Sport, 2023)
Insulin resistance is a growing concern worldwide, affecting millions of people and increasing the risk of various metabolic disorders, including type 2 diabetes, cardiovascular diseases, and fatty liver disease. This paper aims to display the symptoms of insulin resistance and the importance of early detection through various diagnostic tests such as fasting insulin levels, oral glucose tolerance tests, and HOMA-IR scores. Despite the high prevalence of insulin resistance, there is currently no known cure for this condition as it is not a disease in itself. However, lifestyle modifications, including exercise and dietary changes, can effectively manage and prevent the progression of insulin resistance and its associated complications. This study emphasizes the importance of raising awareness about insulin resistance and its adverse effects on individuals’ health and the healthcare system’s burden. Early detection and management of insulin resistance can significantly reduce the risk of developing metabolic disorders and prevent serious health complications.